Bomba de calor para desumidificação e aquecimento do ar - Luiz, Márcia Ramos (2007)
Different forms of air treatment are used for food drying. It is the purpose of this work to describe both the implementation and instrumentation of a system of heat pump for dehumidifying and heating up the drying air under temperatures higher than room temperature but lower that those employed in resistance dryers promoting, in this way, better product quality. Our pump system consists of an evaporator, a condenser, a thermal expansion valve, and a fan. The heat pump makes use of the energy dissipated by both the condenser and the compressor to heat up the air dehumidified by the evaporator. Our device has been better characterized by its effectiveness in heating up the air as well as by its efficient, drying capacity. Sensors were installed at both the inlet and outlet of the device in order to control relative humidity, dry bulb temperature and velocity. Tests were accomplished to verify airflow velocity at 6,1 m/s and 5,7 m/s. For each case, measurements were taken every 15 min, with entering air parameters under atmospheric pressure with temperatures ranging from 27 and 32 ºC, and relative humidity ranging from 68 to 80%. Analyses of the same parameters were carried out at both the heat pump outlet and along the cooling cycle. An energy-exergetic analysis of the heat pump was completed. Simulations were made with the help of computer programs on EES (Engineering Equation Solver) platforms.For these simulations, the programs were developed based on the following: Law of Mass Conservation, and the First and Second Laws of Thermodynamics. It was then possible to put forward some suggestions for improving the drying process and its instrumentation.